Role of Oral Iron Supplementation in Reducing Breath-Holding Attacks in Children under five years - Sadida Amir; Shakil Ahmad; Muhammad Usman; Imran Sarwar; Nisar Khan Sajid; Tanveer Ahmad (Aziz Fatimah Medical and Dental College, 2021)
Objective: To evaluate the effect of oral iron supplementation in the reduction of severity and frequency of breath-holding spells(BHAs) in children under five years. Methodology: This prospective interventional study included 50 patients aged 6 to 60 months with breath-holding attacks and concomitant iron deficiency anemia. It was conducted at independent medical college, from December 2012 to March 2013 after taking ethical approval. All information concerning it was recorded on predesigned proforma and anemia was determined in lab investigation. All patients prescribed oral elemental iron at 6mg/kg/day in two divided dosages for 12 weeks were followed every 4 weeks. On completion of 12-weeks of iron therapy, patients were assessed for reduction or remission in frequency and severity of breath-holding attacks. Results: The majority of children with BHAs (74%) presented during the first 18 months of life. Age of onset of BHAs was predominant in the 06 to 11 months age group (50%). Male children had a higher percentage of BHAs (74%) than females. The frequency of BHAs per week was up to 10 episodes in most children (76%). The cyanotic subtype of BHA was seen in 96% of cases with 66% being severe BHAs. Moderately severe iron deficiency anemia was a predominant finding (70%). The majority of children (95.65%) reported no adverse events with iron supplementation. 91.30% of children showed a complete response with no attacks while 8.69% showed a good response. There was a complete resolution of severe BHAs with only 8.69% remaining in the not-severe BHAs category. Conclusion: Frequency and severity of breath-holding attacks in iron deficient children are effectively reduced after treatment with oral iron supplements